Wickerhamomyces anomalus fungal keratitis responds to topical treatment with antifungal micafungin. Issue 2 (February 2015) - Kamoshita, Mamoru; Matsumoto, Yukihiro; Nishimura, Kazuko; Katono, Yasuhiro; Murata, Mitsuru; Ozawa, Yoko; Shimmura, Shigeto; Tsubota, Kazuo
Abstract We describe a 91-year-old woman who suffered from fungal keratitis after corneal transplantation. The causative organism was identified as Wickerhamomyces anomalus (formerly Pichia anomala or Hansenula anomala) on the basis of morphological characteristics and the sequence of the internal transcribed spacer region of the ribosomal RNA gene. The patient was successfully treated with topical micafungin (MCFG) only. We present the first report of a case of W. anomalus fungal keratitis that responded to topical treatment with the antifungal MCFG.